Efficient Allocation of a Multi-Purpose Sample - Kish, Leslie (Econometrica, 1961)
SUMMARY WHEN LISTING addresses within sample blocks for surveys the field interviewer hastily assigns economic ratings of L, M, and H (for low, medium, and high) to dwellings. The means and the standard deviations differ greatly among these strata with regard to socioeconomic characteristics; hence they may be used for allocating different sampling rates to decrease the variance of sample means and totals. Disproportionate sampling rates bring gains in precision for the means of skewed financial items and for estimates based on higher economic subclasses, but they bring losses in estimating most proportions. The many diverse purposes of economic surveys lead to conflicting allocations. To facilitate rational decision among them we developed condensed ways of analyzing and presenting data. The tables display for many variables the relative precision of several allocation schemes, including the optimum one. Standard statistics are extended to provide estimators for subclasses from stratified samples. Then these are used to investigate optimal and other allocations for the subclasses.